INNOVATIVE TREATMENT TECHNIQUES IN POLYCYSTIC OVARY SYNDROME (PCOS) - Cristina Raluca Iorga; Ana Magdalena Bratu; Camelia Ana Grigore; Adrian Beznea; Adrian Petru Radu; Cristian Iorga; Mihaela Alina Calin (Romanian Society of Oral Rehabilitation, 2023)
Polycystic ovary syndrome (PCOS) is a common condition among women in the fertile period and can have a wide range of symptoms including menstrual disorders, infertility, and, excessive hair growth and metabolic problems. PCOS treatment may vary depending on individual symptoms and patient goals, some of the emerging technologies and innovative approaches that have been investigated in the context of PCOS treatment are: laser therapy for ovarian cysts (HIFU), focused high-intensity ultrasound therapy, gene therapy , stem cell treatment , nutrigenomics and personalized diet , etc , artificial intelligence (AI) interventions. Each technique brings with it promises and challenges, and their implementation in clinical practice requires extensive clinical studies and attention to detail. It is essential to keep the balance between innovation and safety in order to ensure real benefits for patients. Despite the early stage of much research, these innovative approaches pave the way for more efficient and personalized PCOS management.